The impact of the application of knowledge economics in the Kingdom of Saudi Arabia - Idris, Elsadig Adam (Journal of Economic, Administrative and Legal Sciences, 2019)
This study dealt with the impact of the application of knowledge economics in the Kingdom of Saudi Arabia on the increase of revenues according to Vision 2020 of Electricity Company، comparing with Sudan case. The study problem was to measure the effect of using digital counter in Saudi Arabia. The historical approach, the comparative approach and the deductive approach were followed. The most important findings of the study were: There is a positive relation between using Knowledge economics and Increasing revenue, reducing administrative and financial expenses. The study recommended that knowledge economies should be applied in Saudi Electricity Company to structure jobs, reduce administrative expenses, improve the job quality and financial performance by increasing revenues by retrieving debts from individuals, bodies, institutions and governmental bodies, and to be the cornerstone for launching the Kingdom towards the application of knowledge economics in all economic fields, and in all governmental sectors.
Keywords: economy; knowledge economy; public revenues